PENGARUH LATIHAN CATCH AND DROP PUSH-UP TERHADAP HASIL TOLAK PELURU SISWA PUTRA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 5 PEKANBARU - rizal, Tuas; Ramadi, Ramadi; vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract.: The purpose of this research is to find out if there is the influence of the catch and a push-up to the results rejected by a bullet to the students the son of SMK the state 5 pekanbaru, so at the time of rejection a bullet gets you a good result. The research is research to the treatment of (Experimental), the population of this research is students state 5 in Pekanbaru, in this study is the whole population of the eight people. Instrument is used in this study is a test of rejected by a bullet, which aims to measure the ability of the results rejected, data processed by the statistics to test normality with a liliefors with the standard of significant, 0,05?. This hypothesis put forward is the influence of the catch and a push-up to the results rejected by the students the son of SMK state 5 pekanbaru. Based on analysis of statistics, producing data free test of Lcount of 16,31 and data post test Lhitung0, 17,36 Ltabel of 0.285 means Lhitung <Ltabel the data the distribution normal with an increase of 0, 75 based on analysis of the T and obtained Thitung, 3,79 and Ttabel 1,895, Thitung> Ttabel. it was concluded that Ho Horejected and Hi be accepted, this gives the conclusion that there is a significant influence between the catch and a push-up to the results rejected by the students vocational high schools (vocational) state of 5 pekanbaru.Keywords : Catch And Drop Push-Ups, The Rejection